The impact of instrumental feeding on children's responses to taste exposure. Issue 5 (17th December 2012) - Añez, E.; Remington, A.; Wardle, J.; Cooke, L.
Abstract Background In a recent study, we showed that nonfood incentives combined with taste exposure increase children's acceptance of vegetables. However, the impact of children's previous experience of receiving food rewards is unknown. The present study investigated whether the experience of food rewards affects responses to an exposure‐plus‐reward intervention. Methods One hundred and thirty‐seven parents of 4–6‐year‐old children taking part in an exposure‐based intervention study completed an instrumental feeding (IF) questionnaire aiming to assess their use of food rewards. Based on these scores, children were categorised as frequently or rarely instrumentally‐fed. Intervention groups were given 12 daily tastes of a target vegetable combined with no reward, a tangible reward, (sticker) or a verbal reward (praise). A no‐treatment control group received no tastings. Liking and intake of a target vegetable were measured at baseline and post‐intervention. Results Irrespective of experience of IF, children in all intervention groups increased liking compared to controls (all P < 0.001) and both reward groups increased intake compared to controls (both P < 0.05). However, in the nonrewarded exposure group, only children with a limited experience with food rewards increased consumption (P < 0.05). Conclusions Experience of IF may limit the benefits of 'mere exposure'. However, exposure with nonfood rewards can increase the acceptance of vegetables, regardless of previous experience.